Choice of marketing outlets among smallholder cowpea farmers in Ghana. Issue 3 (9th March 2021) - Kotey, Millicent Adei; Adams, Faizal; Nimoh, Fred; Osei Mensah, James; Etuah, Seth; Edwin, Coleman
Abstract : Purpose: To help address the problem of imperfections in the performance of cowpea markets in Ghana, the study sought to understand the costs and benefits associated with different market outlets and factors influencing farmers' choice of these outlets. Design/methodology/approach: A two-stage sampling technique was adopted to collect data from 300 cowpea farmers through purposive sampling of communities and simple random selection at the farmer level in Ejura Sekyedumasi municipality of Ghana. Analytical methods including profitability measures such as gross margin, net margin, return on investment and multinomial logistic (MNL) regression model were used to analyze the data. Findings: The results showed that production and marketing of cowpea is profitable with farmers who trade in wholesale markets recording the highest gross margin (Gh₵1245.85 (US227.76)), net margin (Gh₵1029.37 (US188.18)) and return on investment (ROI) of 63%. Important nonfarm-related factors including household size, farming experience, membership of farmer-based organization and extension contact were found to significantly influence the choice of marketing outlets in the study area. In addition, market attributes such as produce selling price, volume of cowpea sold and post-harvest value addition were also key determinants of cowpea market outlet choices. Practical implications: The results of the study are vital to agricultural administrators in devising efficient cowpea market systems for smallholder farmers in Ghana. Likewise, the study provides important information to smallholder farmers in the choice of market outlets that maximizes their returns. Originality/value: Previous studies on marketing of cowpea in Ghana emphasized on direct retail or consumer marketing to maximize farmers' returns. Meanwhile, there are claims to suggest that the sale of cowpea grains in the country are carried out through varied market outlets which come with differing costs and benefits implications for smallholder farmers. Therefore, the present study comprehensively compared associated costs and benefits in all available cowpea market outlets so as to settle the confusion surrounding most profitable and efficient marketing channel for smallholder farmers toward poverty reduction.